Business communication - Lagare, Rexcel (Burlington, ON, Canada Toronto Academic Press, 2024)
This book introduces the readers to the basic concepts of business communication. It sheds light on the business communication, verbal and nonverbal communication, listening in business communication, group communication, business letters and report writing, public speaking and presentation skills, and communication, technology and challenges. The first chapter explains the introduction to the business communication. It also provides highlights on the evolution of business communication. Purpose of communication in business, importance of the business communication, types of communication methods, and its principle have also been discussed towards the end of this chapter. The second chapter takes the readers through the verbal and nonverbal communication in business. It will provide knowledge about various types of verbal communication, importance of verbal communication, different functions of verbal and no-verbal communication. Towards the end, this chapter talks about the relationship between verbal and nonverbal communication. After that, the third chapter explains about the listening in business communication. Also, it talks about the Differences Between Hearing and Listening, different types of listening, traits of a good listener. Later, various levels of listening, barriers to effective listening also discussed to give a clear insight to reader. The fourth chapter provide insights on the significance of group communication. It also explains the Evolution of the Study of Group Communication, types of group communication, and group decision - making techniques. Importance of group communication in meeting, group communication in media management has also been discussed later in the chapter. Then the fifth chapter introduces the readers to the concept of business letters and report writing. Also, the chapter explains the purpose of a business letter and report writing, essentials for a good business letter, different types of business letters, and different types of report writing in business. The sixth chapter sheds light on the public speaking and presentation skills. It talks about the types of public speaking, types of special occasion speech-es, transactional model of public speaking. In addition, the chapter also discusses about the dialogic theory of public speaking. In the last chapter of this book, it discussed about the communication, technology and challenges. The technology in business communication, importance of technology in business, different communication networks have also been discussed. Towards the end of this chapter, the impact of the internet in business communication, advantages of using the internet in business communication have also been explained. This book has been designed to suit the knowledge and pursuit of the researcher and scholars and to empower them with various aspects of business communication so that they are updated with the information. I hope that the readers find the book explanatory and insightful and that this book is referred by the scholars across various fields.
1. Introduction to Business Communication -- 2. Verbal and Nonverbal Communication -- 3. Listening in Business Communication -- 4. Group Communication -- 5. Business Letters and Report Writing -- 6. Public Speaking and Presentation Skills -- 7. Communication, Technology and Challenges.
Includes bibliographical references and index.
Keywords: Business communication